Моделювання бізнес-процесів сільськогосподарських підприємств - Трусова, Наталя Вікторівна; Вініченко, І. І.; Дьяченко, Н. К.; Trusova, Natalia (Київ : 2022, 2022)
UA: В статті розглянуто теоретичні та методичні положення моделювання бізнес-процесів сільськогосподарських підприємств. Доведено, що моделювання поточних бізнес-процесів сільськогосподарських підприємств в поточному періоді, на основі яких формується оптимізаційна багатокритеріальна граф-модель ймовірного часового лагу дебіторської заборгованості, диференціює параметри ефективності виробничої діяльності шляхом використання методу логістичної регресії. Обгрунтовано, що моделювання бізнес-процесів сільськогосподарських підприємств в поточному періоді дозволяє виявляти причинно-наслідкові зв'язки в дисфункціях виробничої діяльності і переходити до моделі стійкого розвитку з ефективним використанням ресурсних потоків. Моделювання розглядається як рефлексивна технологія, яка на ранніх стадіях розвитку кризових ситуацій виступає методичною основою моделі, яка пов'язує сучасний аналітичний процес та динамічною економічною дійсністю сільськогосподарських підприємств. Для визначення ймовірності часового лагу дебітором заборгованості за продукцію (роботи) послуги представлено економетрично-регресійну модель, яка уособлює комплекс показників результативності. Встановлено, що ефективність впровадженої кредитної політики грунтується на факті досягнення оптимального часового лагу дебіторської заборгованості. EN: The article considers the theoretical and methodological provisions of modeling business processes of agricultural enterprises. It is proved that modeling of current business processes of agricultural enterprises in the current period, based on which the optimization multicriteria graph-model of probable time lag of receivables is formed, differentiates the parameters of production efficiency by using the method of logistic regression. It is substantiated that the modeling of business processes of agricultural enterprises in the current period allows identifying causal links in the dysfunctions of production activities and moving to a model of sustainable development with efficient use of resource flows. Modeling is considered as a reflective technology, which in the early stages of crisis development is the methodological basis of the model, which connects the modern analytical process and the dynamic economic reality of agricultural enterprises. It is substantiated that in the modeling of the current business process there are commodity, energy, labor, logistics and other flows, but all of them in the resource aspect, are also reduced to the primary flows of agricultural enterprises. The existence of primary flows of agricultural entities has a significant result of operation, if the studied object depends not only on the optimization of the use of financial, material and information resources, but also on the components of the relevant flows. The scheme of realization of methodical position on modeling of business processes of agricultural enterprises in the current period is presented. The structure of graph-model of rational architecture of probabilistic time lag of receivables in the current business process of agricultural enterprises is constructed. A system of indicators for evaluating the priority business process of "Probabilistic time lag with receivables" has been developed. To determine the probability of time lag, the debtor of the debt for products (works) of the service presents an econometric model using log-regression, which includes a system of indicators for assessing debtors. It is established that the effectiveness of the implemented credit policy is based on the fact of achieving the optimal time lag of receivables.
Modeling of the business processes of agricultural enterprises
Keywords: моделювання; бізнес-процеси; виробнича діяльність; ресурсні потоки; сільськогосподарські підприємства; modeling; business processes; production activity; resource flows; agricultural enterprises